Equality in Institutional Practice: The Treatment of Member States by EU Institutions - Sehnálek, David (Unequal Equals? The Status of Member States in an Integrating European Union, 2026)
The Chapter addresses the issue of the equality of Member States before EU institutions, based on the rule of law. The EU subscribes to six fundamental principles of the rule of law: legality, legal certainty, prohibition of arbitrary exercise of power, effective judicial protection, separation of powers and equality before the law, as enshrined in Art. 2 TEU. The author points out that while the EU consistently monitors Member States’ compliance with the rule of law, less attention is paid to whether the EU itself complies with this principle. Member States have ceded part of their sovereignty to the EU, trusting that the EU institutions will treat them all fairly and equally. The key question of this chapter is therefore ‘Are EU Member States truly equal before its institutions?’ The study does not focus on legal differences arising from legislation, such as different contributions to the EU budget or different levels of funding from the funds, nor does it address the issue of unequal representation of Member States in the institutions (for example, the ratio of MEPs in the European Parliament). A key question is whether EU institutions treat all Member States according to the same rules. The study concludes that there is currently no reason to suspect the European Parliament of treating Member States differently. This institution does not have the power to adopt decisions that could lead to discrimination between Member States. Its influence is limited to political resolutions, which are not legally binding. However, its increasing politicisation and increasing competences may pose a risk in the future. Nor does the European Council have significant powers to treat Member States unequally. For inequality to manifest itself where it does have powers, i.e. in the Art. 7 TEU procedure, the unanimity of voting is a safeguard. By contrast, the Council can exercise considerable discretion, particularly in matters of fiscal discipline. For example, it has so far refrained from imposing sanctions on Germany and France for breaching the rules of fiscal responsibility, whereas it would be unlikely to do so against other states. As the ‘guardian of the treaties’, the European Commission should be a guarantor of equal treatment. However, its practices show its politicisation, leading to the uneven enforcement of EU law and principles across Member States. While some states face severe measures, others are tolerated. This shift from a technocratic to a political body, resulting from changes in the Commission’s conceptualisation of its mission, increases the risk of inequality. The CJEU on the other hand is a true guarantee of equality between Member States. The CJEU rules independently and ensures a uniform interpretation of EU law. While subordinate to the EU law, Member States are equal among themselves in their jurisprudence. The study confirms that formally Member States are legally equal, but in practice there are differences. The greatest problems relate to the Council and the Commission, where historical cases show the different treatment. Some states are privileged, while the others are subject to more stringent scrutiny. The politicisation of the Commission increases the risk that it will not be able to act impartially in the future. Paradoxically, the growing inequality between Member States is a direct result of the EU’s well-intentioned transformations. The desire to address the EU’s democratic deficit has led to the Commission being more closely tied to the Parliament. However, this has unintentionally and inadvertently led to the Commission being seen less as a neutral, technocratic and professional body and more as the political equivalent of national governments. Careful monitoring of changes to the powers of the European Parliament and the Commission when primary law is amended is therefore essential in the future, as their increasing politicisation could lead to a systematic erosion of the equality of Member States before the EU institutions.